PENGGUNAAN GADGET YANG TEPAT BAGI ANAK USIA SEKOLAH DI SEKOLAH DASAR St. YOSEPH III KOTA KUPANG - Maryati Agustina Barimbing (Jurnal Pengabdiaan Masyarakat Kasih (JPMK), 2021)
In this globalization era, everyone uses gadgets with modern technology such as laptops, computer, tablets, smarthphones and others. Interesting things of gadgets such as social media and online games make gadgets are nedded for all of ages including school-age children. More fun of gadgets activity makes school-age children play gadgets more than two hours a day. Excessive intensity is very dangerous because dependence of gadgets affects intellectual and emotional intelligence, decreased focus on learning, does not do homework, and unable to manage time for others things. More severe impact is the risk of mental disorders. The aim of this community service activity was that students know how to use gadgets correctly and avoid gadgets abuse. The provision of health education was carried out directly to the students in St. Yoseph III Elementary School. Media used are educational videos, posters and leaflets. Students were divided into several groups based on grade level. After providing health education, we evaluated the students’knowledge. The result showed that 65% of students understood the health education and 55% gave positive feedback. It is very important for students to understanding the correct use of gadgets, so that students do not dependence of gadgets which has impact on physical and psychological health problems and does not interfere students’learning processes. Therefore, it is recommended that parents and teachers can monitor the use og gadgets and guide children on how to use gadgets properly both at home and at school. Key Words: Gadgets, School-age children